Reading David : a mother and son's journey through the labyrinth of dyslexia - Weinstein, Lissa; Siever, David (New York : Berkley Pub. Group, 2003)
Lissa Weinstein chronicles her efforts to help her son deal with the emotional and mental challenges of dyslexia.
"A Perigee book."
Adult
Adult
Keywords: Dyslexic children -- Education -- Case studies; Dyslexia -- Case studies; Special education -- Parent participation -- Case studies; Siever, David; Dyslexic children -- Education -- Case studies; Dyslexia -- Case studies; Special education -- Case studies; Education -- Parent participation -- Case studies; Siever, David